Reusable BNPs‐SiO2@(CH2)3NHSO3H‐catalysed selective oxidation of sulfides to sulfones. (7th October 2018) - Bahrami, Kiumars; Khodamorady, Minoo
Abstract : Reusable boehmite nanoparticles–silica–NHSO3 H (BNPs‐SiO2 @(CH2 )3 NHSO3 H) was found to be an efficient heterogeneous nanocatalyst for the selective oxidation of sulfides to sulfones in the presence of H2 O2 . Excellent yields, easy and quick isolation of products, short reaction times and excellent selectivity are the main advantages of this method. The catalyst was characterized using Fourier transform infrared spectroscopy, energy‐dispersive X‐ray analysis, X‐ray diffraction, and transmission and scanning electron microscopies. Abstract : Reusable boehmite nanoparticles–silica–NHSO3 H (BNPs‐SiO2 @(CH2 )3 NHSO3 H) was found to be an efficient heterogeneous nanocatalyst for the selective oxidation of sulfides to sulfones. Excellent yields, easy and quick isolation of products, short reaction times and excellent selectivity are the main advantages of this reaction. The catalyst was characterized using various techniques.